Community input in a genomic health implementation program: Perspectives of a community advisory group - Vidgen, Miranda E.; Cutler, Katrina; Bean, Jessica; Bunker, David; Fowles, Lindsay F.; Healy, Louise; Hondow, Gary; Istiko, Satrio Nindyo; McInerney-Leo, Aideen M.; Pratt, Gregory; Robins, Deborah; Waddell, Nicola; et al. (Frontiers in Genetics, 2022)
Consumer and community engagement (CCE) in the implementation of genomics into health services and associated research is needed to ensure that changes benefit the affected patients. Queensland Genomics was a program to implement genomics into a public health service. We describe its Community Advisory Group’s (CAG) structure and function and provide recommendations based on the CAG members’ perspectives. The CAG provided advice to the Queensland Genomics program and its projects in an advisory capacity. The CAG was also resourced to develop and lead community-focused activities. Key enablers for CAG included; diversity of CAG members’ skills and experience, adequate resourcing, and the CAG’s ability to self-determine their direction. The CAG experienced limitations due to a lack of mechanisms to implement CCE in the Program’s projects. Here, we provide insights and commentary on this CAG, which will be useful for other initiatives seeking to undertake CCE in genomic research and health care.